Makotek sebagai Pelestarian Budaya dan Daya Tarik Pariwisata Budaya di Desa Munggu, Mengwi, Badung. - Rai Suastini; Made Novita Dwi Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The purpose of this research is to examine historical sources, cultural preservation, meaning, and the potential of the Makotek tradition to be developed as cultural tourism. The method used in this research is qualitative method. Primary data were obtained from interviews with several informants who were selected by purposive sampling, while secondary data were obtained from online publications. This study provides recommendations for culture-based tourism to be a very potential option to be developed in Munggu village, Badung regency. The potential for implementing the Makotek tradition as a cultural tourism destination can be seen from its cultural attractions and is supported by adequate accessibility, supporting facilities and good tourism institutions or organizations.Keywords: Makotek, Cultural Preservation, Cultural Tourism